Evaluation Of Total Quality Management In The Achievement Of Quality Of Ma'had Al-Jami'ah IAIN Curup In The Middle Of The Covid-19 Pandemic - Suhirman Suhirman; Muhammad Abdu; Sirajudin Sirajudin; Azwar Rahmat (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2022)
This study aims to evaluate Total Quality Management in Achieving Quality of Education in Ma' Had Aljamiah IAIN Curup in the Midst of the Covid-19 Pandemic. Research data obtained through interviews, observation, and documentation. Informants were selected purposively, and the adequacy of the data used purposive sampling technique. Research informants include the director and secretary of ma'had, and ustadz and mahasantri. Analysis of research data using a qualitative descriptive approach. The results of this study indicate that Ma'had Alajmiah IAIN Curup is in the good category. This is shown from the results of the well-implemented planning, implementation, evaluation and follow-up processes, as well as internal communication that runs synergistically. The achievement of the quality of education, especially learning outcomes is less than optimal with the application of semi-online learning. This is due to the condition of students in terms of psychology, geography, availability of facilities and unstable network conditions. Strategic steps taken to achieve quality education as stated in the principles of Total Quality Management by implementing continuous improvement processes, fostering a quality culture, focusing on customers, internal marketing, professionalism and focusing on customers. As well as formulating strategic steps in the form of quality organization, quality assurance, continuous quality improvement and public accountability, user satisfaction and related parties in achieving the quality of education.